Entrance, Swastik Court - Ayan Ghosh (2023)
Swastik Court, 132 Maharshi Karve Road, Churchgate. Designed by the architectural firm Sykes, Patkar, and Divecha. Varjiwandas Motilal Saraiya, the original owner, named the building ‘Swastika’, an auspicious symbol widely revered in several South Asian cultures.